The influence of astrocytes in synaptic plasticity in mice hippocampal region : modulation by BDNF and adenosine A2A receptors - Macau, Renata Isabel Pacheco (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2018